KEGAGALAN PATAH MATERIAL PADA KONSTRUKSI BAJA AKIBAT KONDISI KERJA YANG BURUK - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
Advanced in the field of fracture mechanics have helped to offset some of the potential dangers posed by increase technologycomplexity. Our understanding of how materials fail and our ability to prevent such failures has increased considerably since World War II. Much remains to be learned, however, and existting knowledge of fracture mechanics is not always applied when appropriate. In the first instance, existing procedures are sufficient to avoid failure, but are not followed by one ore more of the parties involved, due to human error, ignorance, or willfull misconduct. Poor workmanship, inappropriate, or substandard materials, error in stress analysis, and operator error are examples of where the appropriate technology and experience are available, but not applied.